Influência do estímulo verbal no tempo do teste de escada - Ambrozin, Alexandre Ricardo Pepe [UNESP]; Silva, Karlla Janaina Ribeiro da (My University, 2011)
Introduction: The stair-climbing test (SCT) is considered a submaximal test of simple implementation and easy access, which assesses the individual’s functional capacity. Although widely used in surgical patients, there is no standardization regarding the height of the stair and verbal stimulus. Objectives: It was determine if verbal stimulus changes the stair-climbing time (SCt) in individuals over 50 years-old. We compared oxygenation, blood pressure, pulse, respiratory rate and Borg scale between SCT performed with and without stimulation. Methods: We evaluated individuals with ages greater than 50 years-old that performed two STC (with and without verbal stimulation), in the stair with 44 steps, achieving 7.04 m in height and recording the time to climb the stair. The systolic blood pressure (SBP) and the diastolic blood pressure (DBP), respiratory rate (RR), pulse, oxygen saturation (SpO2 ) and Borg scale were evaluated before and after the tests. The time in the SCT with and without stimulation were compared using the Student test-t and the other variables were compared using the ANOVA test (p<0.05). Results: The average age was 59.75±6,40 years old in the 21 evaluated individuals. The time in the SCT without stimulus was significantly higher than the one with stimulus. The SBP, pulse, RR and Borg scale were significantly increased when compared to the SCT with and without stimulus. Oxygenation and DBP didn´t have significant differences at any time of the study. Conclusions: The time in the SCT was lower when performed with verbal stimulus. The SBP, pulse, RR and Borg scale changed significantly after the SCT with and without stimulus, remarking that this change was greater in the SCT with stimulus.

Introdução: O teste de escada (TE) é um teste submáximo, simples realização e de fácil acesso, que avalia a capacidade funcional do indivíduo. Apesar de muito usado em pacientes cirúrgicos, ainda não há padronização quanto à altura da escada e estímulo verbal. Objetivos: Avaliar se o estímulo verbal altera o tempo do TE em indivíduos acima de 50 anos. E comparar a oxigenação, a pressão arterial, o pulso, a freqüência respiratória e a escala de Borg entre os testes de escada realizados com e sem estímulo. Métodos: Foram estudados sujeitos saudáveis maiores que 50 anos, que realizaram dois TE (sem e com estímulo verbal), em escada composta por 44 degraus totalizando 7,04 m de altura e o tempo foi cronometrado. Antes e após a realização dos testes, foram avaliadas a pressão arterial sistólica (PAS) e diastólica (PAD), a freqüência respiratória (FR), o pulso, a saturação de oxigênio (SpO2 ) e a Escala de Borg. Os tempos durante os TE com e sem estímulo foram comparados por meio do Teste t Student e as outras variáveis comparadas nos momentos de estudo utilizando o teste de ANOVA (p<0,05). Resultados: A idade média dos 21 indivíduos avaliados era de 59.75±6.40 anos. O tempo no TE sem estímulo foi significativamente maior em relação ao com estímulo. A PAS, o pulso, a FR e escala de Borg aumentaram significativamente nos TE com e sem estímulo. A oxigenação e a PAD não apresentaram diferenças significativas em nenhum momento do estudo. Conclusões: O tempo no TE foi menor quando realizado com estímulo verbal. A PAS, o pulso, a FR e a escala de Borg tiveram alteração significativa após o TE com e sem estímulo, sendo que esta alteração foi maior no teste com estímulo.
Verbal stimulus influence at the time stair-climbing test
Keywords: teste de esforço; Testes de Função Respiratória